Pharmaceutical care for patients with tuberculosis and diabetes mellitus in Malaysia: a complex intervention - Gnanasan, Shubashini (2012)
The increasing comorbid burden of tuberculosis (TB) and diabetes mellitus (OM) worldwide requires the management of all stakeholders including pharmacists. This raises the question whether current single disease management system fulfils patients' health needs and whether pharmacists could effectively play a role in enhancing the joint management of these two commonly associated diseases. Pharmacists have begun to provide pharmaceutical care through pharmacist-led medication therapy adherence clinics and clinical pharmacy services for several diseases and conditions (e.g. OM, asthma) in some public hospitals in Malaysia but are yet to be involved in the management of TB. The management of TB has been largely delivered through directly observed treatment (OOT) as high level of adherence to treatment is vital. However, little is known on how TB patients with OM are being managed and how these patients cope with their medication. The aim of this study was to develop a pharmaceutical care service for patients with TB and OM.